Synthesis, Characterization, and Acute Oral Toxicity Evaluation of pH-Sensitive Hydrogel Based on MPEG, Poly(ε-caprolactone), and Itaconic Acid. (30th November 2013) - Tan, Liwei; Xu, Xu; Song, Jia; Luo, Feng; Qian, Zhiyong
Abstract : A kind of chemically cross-linked pH-sensitive hydrogels based on methoxyl poly(ethylene glycol)-poly(caprolactone)-acryloyl chloride (MPEG-PCL-AC, PECA), poly(ethylene glycol) methyl ether methacrylate (MPEGMA, MEG), N, N-methylenebisacrylamide (BIS), and itaconic acid (IA) were prepared without using any organic solvent by heat-initiated free radical method. The obtained macromonomers and hydrogels were characterized by 1 H NMR and FT-IR, respectively. Morphology study of hydrogels was also investigated in this paper, and it showed that the hydrogels had good pH-sensitivity. The acute toxicity test and histopathological study were conducted in BALB/c mice. The results indicated that the maximum tolerance dose of the hydrogel was higher than 10000 mg/kg body weight. No morality or signs of toxicity were observed during the whole 7-day observation period. Compared to the control groups, there were no important adverse effects in the variables of hematology routine test and serum chemistry analysis both in male or female treatment group. Histopathological study also did not show any significant lesions, including heart, liver, lung, spleen, kidney, stomach, intestine, and testis. All the results demonstrated that this hydrogel was nontoxic after gavage. Thus, the hydrogel might be the biocompatible potential candidate for oral drug delivery system.